2018
DOI: 10.1007/s00167-018-5060-x
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal neurovascular bundle is safe during inside-out repair of medial meniscus without a safety incision

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Cuellar et al reported that the risk of lateral meniscal repair is safer at 90° and worse with extension of the knee (Cuellar et al, 2015). Recently, an MRI based study demonstrated the significant risk to the neurovascular structures with repair of the lateral meniscus (Gupta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cuellar et al reported that the risk of lateral meniscal repair is safer at 90° and worse with extension of the knee (Cuellar et al, 2015). Recently, an MRI based study demonstrated the significant risk to the neurovascular structures with repair of the lateral meniscus (Gupta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An overarching concern when performing lateral meniscus repairs by either technique is the safety of the neurovascular structures in this area. Tears medial to the popliteus tendon are preferably repaired using an all-inside device since the popliteus neurovascular structures are not safe by using any portal or cannula type [45]. The all-inside device for posterior repairs must not be inserted from the anterolateral portal.…”
Section: Lateral Meniscus Longitudinal Tearsmentioning
confidence: 99%
“…Nevertheless, meniscus repair has a certain degree of risk of neurovascular injuries, especially in cases with all-inside repair for a tear in the posterior horn of the lateral meniscus (LM). 8 , 9 Some cadaveric or magnetic resonance imaging (MRI) studies showed that repair of the posterior LM through an anterolateral portal increased the risk of popliteal artery injury, 10 , 11 , 12 , 13 , 14 and this was recognized as a relative contraindication. However, performing meniscus repair of the posterior LM from an anteromedial portal to avoid vascular injury requires that a suture device penetrate the meniscus obliquely.…”
Section: Introductionmentioning
confidence: 99%